Perancangan Kawasan Perdagangan dan Jasa Koridor Jalan Sultan Agung Bandar Lampung - Azriel Al-Faridzi; Nia Kurniasari (Jurnal Riset Perencanaan Wilayah dan Kota, 2024)
Abstract. Bandar Lampung City has a strategic position as the gateway to Sumatra, functioning as a transit area between Sumatra Island and Java Island. This supports the growth and development of Bandar Lampung as a trade and service center, so that it is designated as a National Activity Center (PKN) in accordance with Article 10 letter a of Lampung Province Regional Regulation Number 12 of 2019 concerning the Lampung Province Spatial Plan. PKN in Bandar Lampung aims to serve the Province, Southern Sumatra, national and international regions. However, the existing condition of the Sultan Agung road corridor is still not well organized, facing problems such as the absence of pedestrian paths, minimal roadside vegetation, less organized building facades, uneven street lighting, and lack of parking lots. This research aims to identify the characteristics of the Sultan Agung road corridor and develop the design of the trade and service area in the corridor. The methodology used is a mixed method approach, analysis of the area and planning area, and analysis of community-based development. The results of the research are expected to be in the form of formulation and development of design and investment plans in the planning area. Abstrak. Kota Bandar Lampung memiliki posisi strategis sebagai pintu gerbang Sumatera, berfungsi sebagai daerah transit antara Pulau Sumatera dan Pulau Jawa. Hal ini mendukung pertumbuhan dan pengembangan Bandar Lampung sebagai pusat perdagangan dan jasa, sehingga ditetapkan sebagai Pusat Kegiatan Nasional (PKN) sesuai dengan Pasal 10 huruf a Peraturan Daerah Provinsi Lampung Nomor 12 Tahun 2019 tentang RTRW Provinsi Lampung. PKN di Bandar Lampung bertujuan melayani wilayah Provinsi, Sumatera Bagian Selatan, nasional, dan internasional. Namun, kondisi eksisting koridor jalan Sultan Agung masih belum tertata baik, menghadapi masalah seperti tidak adanya jalur pedestrian, vegetasi tepi jalan minim, fasad bangunan kurang tertata, penerangan jalan tidak merata, serta kurangnya tempat parkir. Penelitian ini bertujuan mengidentifikasi karakteristik koridor jalan Sultan Agung dan menyusun perancangan kawasan perdagangan dan jasa di koridor tersebut. Metodologi yang digunakan adalah pendekatan mix method, analisis kawasan dan wilayah perencanaan, serta analisis pengembangan berbasis peran masyarakat (community- based development). Hasil penelitian diharapkan berupa rumusan dan pengembangan perancangan serta rencana investasi pada kawasan perencanaan. .